Analisis Sistem Rekruitmen dan Profesionalisme Terhadap Kinerja Karyawan PT. BANK ACEH SYARIAH Cabang Kutacane - Nasruddin Nasruddin; Rila Maufira (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
PT Bank Aceh Syariah Kutacane Branch. Companies engaged in finance, in the form of capital, namely the provision of savings and loan capital. The number of employees is 22. In this study, the background to the problem is that the recruitment carried out by PT Bank Aceh Syariah has not fully paid attention to needs, so it is difficult to get professional employees which results in low employee performance. This research is descriptive qualitative, data collection method with field research using methods, direct observation and interviews on research objects to obtain an overview of research subjects. The recruitment system run by the company is not fully appropriate, in accordance with the company's goals, where there are still a number of employees who have educational backgrounds and concentrations, who have not been able to demonstrate and contribute to the company. 11 of 2002, regarding the withdrawal system (recruitment) which must use the media as a medium of information. From these conclusions it can be suggested that the recruitment system for the future must be in accordance with the objectives in accordance with standard operating procedures (SOP) so that it is easy to evaluate and measure employee performance. To see the effectiveness of the company's achievements.